Combined microbiome and metabolomics analysis of yupingfeng san fermented by Bacillus coagulans: insights into probiotic and herbal interactions - Kang,Yu; Sun,Yanting; Cui,Jinzhong; Song,Yuzhen; Sun,Zilong; Li,Huan; Niu,Ruiyan; Qiao,Hongxing (PeerJ, 2025)
Background Yupingfeng san is a traditional Chinese medicine formula composed of siler, atractylodes, and astragalus. The herbal medicine fermentation process relies on the role of probiotics. Bacillus coagulans is a probiotic commonly used to ferment food and drugs. It produces a variety of beneficial metabolites during fermentation. However, the study on the interaction between B. coagulans and yupingfeng san is still blank. Methods During solid-state fermentation of yupingfeng san, we used metabolomics technology and 16S rDNA sequencing to analyze the differential metabolites and microbial flora of B. coagulans at 0, 3, 7, 11, and 15 d, which corresponded to groups A0, B3, B7, B11, and B15, respectively. This research explored the correlation between microorganisms and metabolites in fermented compound Chinese medicine. Results The results revealed a significant difference in species β diversity between group A0 and the B groups (P < 0.01). At the phylum level, in fermentation groups B3, B7, B11, and B15, the Cyanobacteria relative abundance decreased by 6.69%, 9.09%, 5.74%, and 2.24%, respectively (P < 0.05). The Firmicutes relative abundance increased by 39.73%, 35.65%, 49.09%, and 68.66% (P < 0.05), respectively. The Proteobacteria relative abundance decreased by 39.86% and 26.70%, respectively, in groups B11 and B15 (P < 0.05). The relative abundance of Actinobacteria increased initially with extended fermentation time, and then gradually decreased after reaching its peak in group B7. At the genus level, compared with group A0, the relative abundance of Actinobacteria increased to its highest level of 21.12% in fermentation group B3 and decreased to 9.51% after a fermentation time of 15 d. The abundance of Leuconostoc in fermentation groups B3, B7, and B11 was significantly higher than in group A0 (20.93%, 20.73%, and 21.00%, respectively, P < 0.05). Pediococcus in fermentation groups B3, B7, B11, and B15 was also significantly higher than in group A0 (4.20%, 2.35%, 18.84%, and 52.01%, P < 0.05). Both Pediococcus and Leuconostoc, which belong to lactic acid bacteria, increased fivefold, accounting for a total abundance of 62%. After yupingfeng san fermentation, using nontargeted metabolomics, we identified 315 differential metabolites. This results showed a decrease in the content of alkene and an increase in the contents of acids, lipids, ketones, and amino acids. In addition, in group B3, the contents of quercetin, paeoniflorin-3-O-glucoside, netin, iristin, anthocyanin, caffeic acid, rosmarinic acid, liquiritin, and isoliquiritin were significantly upregulated. Conclusion In this study, the composition and metabolic profile of yupingfeng san after the fermentation of B. coagulans were studied, and it was found that the fermentation group showed rich species diversity, in which the abundance of Leuconostoc and Weisseria increased significantly, while the opportunistic pathogens such as Pseudomonas aeruginosa and Enterobacter decreased significantly. The analysis of metabolic products showed that the contents of acids, lipids and ketones were significantly increased, rich in a variety of beneficial microorganisms and small molecular compounds with antibacterial effects, and these changes worked together to inhibit the growth of pathogens and maintain intestinal health. The study not only helps to elucidate the assembly mechanism and functional expression of microorganisms after Chinese traditional medicine fermentation, but also provides a solid scientific basis for the development of efficient and safe micro-ecological feed additives.
Keywords: Yupingfeng san; Bacillus coagulans; Solid state fermentation; Metabolomics; Species diversity; Correlation analysis